Urinary Cadmium Level Causing Impaired Kidney Function in Farmers in Gintungan Village, Bandungan District - Poppi Nastasia Yunita Dewi; Nurjazuli Nurjazuli; Budiyono Budiyono (Universitas Airlangga, 2022)
Introduction: Farmers apply pesticides to control pests on vegetable farming in Semarang regency. One of the active ingredients of pesticides is cadmium (Cd), and exposure to cadmium in humans can interfere with kidney function. High exposure to Cd may cause the effects of chronic kidney failure. If there are a lot of free Cd ions in the body, the ability of the kidneys to produce metallothionein will be reduced. Thus, it may damage the kidney tubules as it results in high levels of urinary Cd which can be toxic. This study aimed to analyze an association between the levels of urinary Cd and impaired kidney function in farmers. Methods: This study was analytic observational and used design a cross-sectional study design. The population in this study was all farmers as many as 406 people in Gintungan village, Bandungan district, Semarang regency. There were 60 people selected as samples through purposive sampling. Results and Discussion: The level of urinary Cd in farmers on average was 0.958 µg/L with a standard deviation of 0.570 µg/L. The highest level of Cd was 5.390 µg/L and the lowest was < 0.100 µg/L. The results of the statistical chi-square test showed there was an association between levels of urinary Cd and impaired kidney function (p = 0.041). Conclusion: Impaired kidney function in farmers in Gintungan might be caused by the level of urinary Cd. Further research should measure creatinine in the blood to ensure a decrease in the glomerular filtration rate in the kidneys of the farmers.